2009
DOI: 10.1111/j.1440-1681.2008.05116.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Composition of the Thoracic Aortic Wall in Spontaneously Hypertensive Rats Treated With Losartan or Spironolactone

Abstract: 1. In the present study, we compared the elastin and collagen content of thoracic aortic medial and adventitial layers from Wistar-kyoto (WKY) and spontaneously hypertensive rats (SHR). In addition, the effects of losartan, an angiotensin II receptor antagonist, and spironolactone, a mineralocorticoid receptor antagonist, on collagen and elastin content were determined. 2. Prehypertensive (4-week-old) and hypertensive (16-week-old) SHR were randomly divided into three groups treated with either 0.9% NaCl, losa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 28 publications
3
20
1
Order By: Relevance
“…The present study showed that maximum stiffness was reduced after adventitial removal in WKY and SHR at both ages, indicating that adventitial layers play a contributory role in vascular biomechanical properties. This finding is consistent with our previous study showing that there were abundant densely distributed collagen in Sirius Red Staining, and hydroxyproline measurement showed that adventitial layer collagen was comparable to that in the medial layer [12] . These finding indicated that adventitial layer might be a pharmacological target in the prevention and treatment of cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The present study showed that maximum stiffness was reduced after adventitial removal in WKY and SHR at both ages, indicating that adventitial layers play a contributory role in vascular biomechanical properties. This finding is consistent with our previous study showing that there were abundant densely distributed collagen in Sirius Red Staining, and hydroxyproline measurement showed that adventitial layer collagen was comparable to that in the medial layer [12] . These finding indicated that adventitial layer might be a pharmacological target in the prevention and treatment of cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 82%
“…In 2-kidney 1-clip hypertensive rats, carotid arteries were stiffer after 9 and 24 weeks, but no stiffening had occurred at 1 and 5 weeks after renal artery clipping [23] . In consistent with these above findings, the present study showed that there was no significant difference between SHR and WKY at the age of 16 and 32 week in terms of elastic stiffness and maximum stiffness in intact thoracic aorta, or in thoracic media (without adventitia), which is consistent with our previous finding that elastin : collagen ratio in thoracic media and adventitia was not changed in SHR and WKY, although there is significant medial remodeling in 16-and 32-week old SHR compared with age-matched WKY including increased mass, collagen and elastin content, thoracic adventitial collagen [12] . These results indicated that elastin : collagen ratio may be the determinant of vascular stiffness [24][25][26] .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…They found that both collagen and elastin synthesis (as revealed by specific hydroxyproline activity) exceeded WKR control levels in the prehypertensive period (at the age of 4 weeks ), decreased in the development of hypertension (to the age of 14-16 weeks), and increased again in the period of the established hypertensive state (beyond the age of 16 weeks). Several studies showed that this second increase in connective tissue proteins may be prevented, depending on the choice of antihypertensive therapy (Tsoporis et al, 1998;Han et al, 2009).…”
Section: Discussionmentioning
confidence: 99%